A method for identifying and repairing holes on the surface of unorganized point cloud. (31st March 2023) - Zhang, Chaolong; Zhou, Haibo; Duan, Ji'an
Highlights: A new hole identification algorithm for unorganized point cloud is proposed. Multiple types of holes in the point cloud are identified and segmented accurately. Holes are repaired by a fuzzy system with geometry and feature information. The quality and efficiency of the hole repairing algorithm are taken into account. Abstract: During scanning, reflection and occlusion of objects, produce holes in the acquired point clouds, causing problems to functions such as map building and target detection. In this paper, a new method for identifying and repairing such holes is proposed. First, the density and the 2D projection points of the point cloud are calculated. Based on the Euclidean distance, the hole boundary points of the original point cloud are obtained. Following, a novel preprocessing segmentation algorithm is used to obtain the boundary points of holes. Next, even if the boundary points are not fully identified, the total 2D repairing points are obtained by the proposed algorithm. Finally, a new hole repairing model, based on fuzzy inference system, is proposed, integrating geometry and curvature information of boundary points, while it can fast and accurately estimate the height coordinates of the repairing points. The experimental results show that the proposed algorithm is efficient.